Studi Literatur Review : Analisis Kemampuan Berpikir Komputasi Siswa Melalui Aplikasi Sebagai Media Pembelajaran - Saprina Maulida; Yahfizham (Universitas Palangka Raya, 2024)
This research aims to comprehensively examine students' computational thinking skills through applications as existing learning media. This research uses the Systematic Literature Review (SLR) method to draw conclusions from the results of research examining mathematical problem solving skills in terms of student self-efficacy. SLR research aims to identify, review, and make conclusions from all research results related to the research topic. Literature collection that becomes research data is done by tracing the results of research published in journals online using the Publish or Perish search engine on Google Scholar and based on inclusion criteria. The results of the literature study that has been carried out, can be concluded that the ability of students' computational thinking through applications as learning media is quite good. The researcher recommends that further research be conducted on existing applications that can help students in learning.